1986
DOI: 10.2105/ajph.76.5.550
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complication rates in first trimester abortions performed by physician assistants and physicians.

Abstract: The outcomes of 2,458 first trimester abortions performed in a freestanding clinic in Vermont were studied. Procedures were performed by physician assistants and by physicians. Demographic information, medical history, and data relevant to the abortion were recorded. Both immediate and delayed (up to four weeks post-abortion) complications were noted. Direct follow-up four weeks after the procedure by clinic visit, letter, or telephone

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 5 publications
2
36
0
Order By: Relevance
“…15 In two US states, Vermont and Montana, physician assistants have been performing surgical abortions since the 1970s. [20][21][22] Finally, in several low-resource settings, nursemidwives and other trained mid-level providers of reproductive health care successfully manage the complications of unsafe abortion through provision of post-abortion care with MVA. 23 Mid-level practitioners provide high quality, safe, surgical abortion care, often without physician supervision.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 In two US states, Vermont and Montana, physician assistants have been performing surgical abortions since the 1970s. [20][21][22] Finally, in several low-resource settings, nursemidwives and other trained mid-level providers of reproductive health care successfully manage the complications of unsafe abortion through provision of post-abortion care with MVA. 23 Mid-level practitioners provide high quality, safe, surgical abortion care, often without physician supervision.…”
mentioning
confidence: 99%
“…15,24 Equivalence studies comparing mid-level and physician provision of surgical abortion (mostly MVA) in both high-and low-resource settings confirm that trained mid-level clinicians competently perform these procedures at the same standard of care as physicians. 18,22,24 Yet, there remains doubt and debate as to whether mid-level clinicians can provide a similarly high level of medical abortion care. This attitude is counter-intuitive, given that performance of surgical abortion requires a higher degree of skill than that required for provision of medical abortion.…”
mentioning
confidence: 99%
“…It was found that with appropriate government training, mid-level healthcare providers can provide first trimester MVA abortions as safely as doctors can. [31][32][33][34][35][36] In Turkey, induced abortion has always been important in fertility regulation, even preceding it's legalisation on socioeconomic grounds in 1983 with the enactment of the new Population Planning Law. In the early 1980s, the growing incidence of unsafe abortion in Turkey and the resulting morbidity and mortality rates led the government to liberalise the law further and make abortion widely available.…”
Section: Scope Of Induced Abortionsmentioning
confidence: 99%
“…A comprehensive analysis of complication rates in 2,456 first trimester abortions done between 1981 and 1982 at the Center found that the complication rates were no different than with abortions provided by physicians. 8 A more recent, as yet unpublished, study by researchers at Planned Parenthood Northern New England compared complication rates for 2,027 procedures by physicians and physician assistants and nurse practitioners at five sites from November 2000 through December 2002. Complication rates for all providers were very low (2.5 per 1,000), and patients reported slightly more satisfaction with nonphysician providers.…”
Section: Medical and Legal Issuesmentioning
confidence: 99%